Considering Pre-service Teacher Disposition towards Mathematics - Cooke, Audrey (Mathematics Education Research Group of Australasia, 2015)
The push to ensure pre-service teachers are numerate, on face value, is appropriate. However, the way in which numeracy is described is of great importance as it will determine what is assessed and potentially how it is assessed. The way numeracy is described will also impact on how pre-service educators assist pre-service teachers to develop their numeracy. This paper proposes that numeracy incorporates mathematical skills and disposition towards mathematics. A discussion of what disposition towards mathematics is and how it may be measured is provided, together with the proposition that addressing pre-service teacher disposition towards mathematics may help pre-service teachers to develop their numeracy – numeracy that reflects willingness to actually use mathematics in the real world. Suggestions on how this may be achieved are outlined.